The use of low-cost Android tablets to train community health workers in Mukono, Uganda, in the recognition, treatment and prevention of pneumonia in children under five: a pilot randomised controlled trial. - O'Donovan, James.; Kabali, Kenneth.; Taylor, Celia.; Chukhina, Margarita.; Kading, Jacqueline C.; Fuld, Jonathan.; O'Neil, Edward. (2018)
Background: Since 2012, The World Health Organization and UNICEF have advocated for community health workers (CHWs) to be trained in Integrated Community Case Management (iCCM) of common childhood illnesses, such as pneumonia. Despite the effectiveness of iCCM, CHWs face many barriers to accessing training. This pilot study compares traditional training with using locally made videos loaded onto low-cost Android tablets to train CHWs on the pneumonia component of iCCM.; Keywords: Community health worker (CHW), Uganda, Pneumonia, mHealth, Mobile technologies, Integrated Community Case Management (iCCM).; Springer Open.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy